A Plain & Simple Heart - Copeland, Lori; Smith, Virginia 1960- (Eugene, Or. : Harvest House Publishers, 2012)
Young Amish woman Rachel Switzer comes to 1880s Lawrence, Kansas in pursuit of cowboy Jesse Montgomery, only to be caught in the middle of a temperance riot and mistakenly arrested by sheriff Colin Maddox.
Keywords: Young women -- Fiction; Sheriffs -- Fiction; Amish -- Fiction -- Kansas; Western stories; Love stories; Christian fiction